Sustainable Management and Community Willingness to Pay for Communal Wastewater Services in Yogyakarta - Hashfi Hawali Abdul Matin; Julianatasya Tantri Damayanti; Siti Rachmawati; Sapta Suhardono; Lia Kusumaningrum; Budiyono Budiyono; Callista Fabiola Candraningtyas (Universitas Diponegoro, 2026)
Domestic wastewater discharge into rivers remains a persistent environmental and public health challenge in rapidly urbanizing regions of developing countries such as China. Although communal wastewater treatment systems have been increasingly implemented, empirical studies integrating community willingness to pay (WTP), behavioral determinants, and sustainability planning are limited. This study analyzes community willingness to pay for communal wastewater treatment services and formulates sustainability-oriented strategies for the Sewon Communal Wastewater Treatment Plant (WWTP) in the Special Region of Yogyakarta, Indonesia. A mixed-methods approach combined a survey of 100 households with interviews and a document analysis. WTP was estimated using the contingent valuation method with a payment card format, while behavioral determinants were examined using covariance-based Structural Equation Modelling (SEM) with AMOS. Strategic formulation was conducted using SWOT analysis supported by IFAS and EFAS matrices based on validated SEM results. The results indicate a positive willingness to pay, with a mean of IDR 7,114 and a median of IDR 7,500. The SEM revealed that supporting institutional factors significantly influenced the WTP (X4 = 0.664; p < 0.01), whereas environmental perception and inhibiting factors were not statistically significant. These findings highlight the decisive role of institutional strength in ensuring the financial sustainability of the communal wastewater service